2022
DOI: 10.1016/j.athoracsur.2021.05.060
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Extracorporeal Membrane Oxygenation in Patients With Severe Acute Respiratory Distress Syndrome Caused by COVID-19 Versus Influenza

Abstract: Background Extracorporeal membrane oxygenation (ECMO) can be effective for refractory acute respiratory distress syndrome (ARDS) in patients with influenza, but its utility in patients with COVID-19 is uncertain. We compared outcomes of patients with refractory ARDS from COVID-19 and Influenza placed on ECMO. Methods We conducted a retrospective analysis of 120 patients with refractory ARDS due to COVID-19 or Influenza placed on ECMO at two referral centers from 1/2013 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 21 publications
(23 reference statements)
2
24
0
1
Order By: Relevance
“…Additionally, overall experience with initiation and handling of vv-ECMO over the study period may also have had an influence. The largest study compared 53 patients with COVID-19 and 67 patients with influenza and did not show significant outcome differences [23]. Duration on vv/va-ECMO and ICU length of stay in this study was significantly longer in patients with COVID-19, which is in line with our findings.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Additionally, overall experience with initiation and handling of vv-ECMO over the study period may also have had an influence. The largest study compared 53 patients with COVID-19 and 67 patients with influenza and did not show significant outcome differences [23]. Duration on vv/va-ECMO and ICU length of stay in this study was significantly longer in patients with COVID-19, which is in line with our findings.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies reported a higher rate of bleeding events in patients with COVID-19 on vv/va-ECMO compared to influenza [21,23]. In our cohort we observed more bleeding complications in COVID-19 than in influenza patients.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…7-9 In reports surrounding the use of ECMO for COVID-19, outcomes remain dismal, with rates of survival to discharge of 62.3%, with longer durations of hospital stay compared to other viral illnesses (37 vs 13.5 days; P = 0.007). 10 Although trajectories of COVID-19 incidence under the influence of vaccine development and mass vaccination efforts have improved, global rates of new cases still exceed 1 million per week, with more than 40 000 new deaths per week. 1…”
Section: Introductionmentioning
confidence: 99%